Kajian Fitokimia, Kandungan Fenolik dan Flavonoid Total, serta Aktivitas Antioksidan Ekstrak Buah Rimbang (Solanum torvum Sw.) - Afrizal Itam; Natasya Dwi Putri; Winda Hardani; Suryati (Departemen Kimia Universitas Andalas, 2025)
Solanum torvum Sw is one of the medicinal plants which is utilized by the community as a food ingredient and herbal medicine. The aims this study is to determine of secondary metabolite compounds, total phenolics and flavonoids content, and antioxidant activity using DPPH method from S. torvum fruit extracts. The results show that S. torvum contains secondary metabolite compounds involves flavonoids, phenolics, steroids, saponins, alkaloids and coumarins. Total phenolic content of hexane, ethyl acetate and aqueous fractions were 49.0, 72.7 and 45.0 mg GAE/g sample, respectively. Meanwhile, total flavonoid content of hexane, ethyl acetate and aqueous fractions were 53.8, 199.2 and 57,7 mg QE/g sample, respectively. Antioxidant activity that expressed with IC50 value were categorized as very powerfull antioxidant to DPPH for hexane and ethyl acetate fractions IC50 37.12 and 2.36 mg/L), while aqueous fraction was categorized strong activity (IC50 84.9 mg/L)